2009
DOI: 10.1007/s11250-009-9435-3
|View full text |Cite
|
Sign up to set email alerts
|

Serological survey of antibodies against BVD virus in camels (Camelus dromedarius) in Iran

Abstract: This serological survey was carried out to detect antibodies in dromedary camels against BVD virus in Iran. A total of 137 serum samples, were collected from camels at Khorein abattoir in suburbs of Tehran and examined for BVDV, using the serum neutralization test (SNT). Twenty seven of the 137 camels (19.7%) were positive for BVDV antibodies. It was found that the rate of seropositive camels in Iran is substantially higher compared to figures published in most other countries. This study indicated an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…In a recent study in Saudi Arabia, BVDV antibodies have been detected in 18% of camels (Al-Afaleq et al 2007). In Iran, BVDV seroprevalence in camels was found to be 19.7% (Afshin Raoofi et al 2009). The BVDV seroprevalence rate is higher in Sudan (84%) than in Egypt (52%).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study in Saudi Arabia, BVDV antibodies have been detected in 18% of camels (Al-Afaleq et al 2007). In Iran, BVDV seroprevalence in camels was found to be 19.7% (Afshin Raoofi et al 2009). The BVDV seroprevalence rate is higher in Sudan (84%) than in Egypt (52%).…”
Section: Discussionmentioning
confidence: 99%
“…Three different pestiviruses have been described, namely, bovine viral diarrhoea virus (BVDV), Border disease virus (BDV) and Classical Swine Fever Virus (CSFV) [36]. BVDV and BDV are widespread throughout the world and sero-epidemiological surveys of both these viruses in Iran showed widespread infection in cattle, sheep and goat populations [37, 38]. Possible transmission of pestiviruses between domestic animals and wild ruminants is considered a risk where they share pastures.…”
Section: Introductionmentioning
confidence: 99%
“…These findings disagreed with the results of Raoofi et al . [ 34 ] who found that the frequency-positive cases were not significantly different between male and female.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a highly significant correlation between the effect of age and incidence of BVDV antibodies, BVDV Ag, and RVFV IgG antibodies in the examined camel serum samples. This might indicate that older animals have a higher exposure to infection and contact could have occurred some years ago [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%